Initial flat ridge impression using compound material on edentulous mandible: Pencetakan awal flat ridge menggunakan compound pada edentulous mandibula - Ainun Bazira; Mohammad Dharma Utama; Adriani Dachri (Makassar Dental Journal, 2024)
Flat ridge condition makes difficult to have a retentive complete denture. This complication can be overcome by the use of com-pound impression material because it can produce denture bearing area moulds. This article discusses flat ridge impression using compound in a case of mandibular edentulus. A 60-year-old man came to the RSGM with complaints of difficulty chewing food due to the loss of all upper and lower jaw teeth and a flat ridge on the lower jaw. The patient wanted to make a comfortable denture. In this case, type 1 compound moulding material was used for the initial moulding. This material is reversible and can be modified to obtain more accurate details. The use of compound materials using the mucocompression moulding technique can print the parts of the lower jaw that move for the expansion of the denture well so that a moulding result is obtained that can provide support for making a denture. It is concluded that the use of compound materials in moulding mandibular edentulous flat ridge can produce a stable and retentive complete denture.